REVITALIZATION OF BIOMASS FUEL BY IMPLEMENTING UB EARTHEN FURNACE TO SUPPORT THE SOCIETY’S SUSTAINABILITY OF ENERGY: A CASE STUDY IN THE SUBDISTRICT OF DAU, MALANG - Suman, Agus; Nurhuda, M. (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2016)
The objectives of this study are to examine the likelihood of society in turning the use of the traditional and gas furnaces to the UB earthen furnace and to examine the potential reduction of the use of firewood and gas furnaces at Dau Subdistrict of Malang. Using descriptive analysis, this study found that the use of UB earthen furnace is able to reduce the use of firewood and gas furnace up to 50% and people’s tendency in willing to turn both firewood and gas furnaces into the earthen furnace increases up to 60% dealing with its benefits and costs which have been observed by several main aspects (including economical, technical, environmental, social, and health aspects).